2008
DOI: 10.15232/s1080-7446(15)30884-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dry Distillers Grains Plus Solubles Inclusion on Performance and Economics of Finishing Beef Steers

Abstract: A 167-d feedlot study was conducted to evaluate feeding increasing levels of dry distillers grains plus solubles (DDGS) to finishing cattle and the impact on performance and profitability. Crossbred steer calves (n = 240, BW = 306 ± 24.5 kg) were used in 30 pens with dietary treatments of 0, 10, 20, 30, and 40% DDGS dietary inclusion (DM basis). Quadratic relationships (P < 0.05) were observed for final BW and ADG as dietary DDGS increased, with the greatest ADG observed at 20% inclusion. The DMI was not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 7 publications
1
31
2
2
Order By: Relevance
“…This is in contrast to Ham et al (1994) and Buckner et al (2008) who noted higher gains on cattle fed corn DDGS relative to those fed a corn-based ration. The lack of response in ADG is consistent with the reduced DMI of the corn DDGS fed cattle as discussed above.…”
Section: Finishing Performancecontrasting
confidence: 85%
See 2 more Smart Citations
“…This is in contrast to Ham et al (1994) and Buckner et al (2008) who noted higher gains on cattle fed corn DDGS relative to those fed a corn-based ration. The lack of response in ADG is consistent with the reduced DMI of the corn DDGS fed cattle as discussed above.…”
Section: Finishing Performancecontrasting
confidence: 85%
“…However, this theory does not explain why DMI is not reduced when corn DDGS is fed in corn-based rations. For example, Buckner et al (2008) did not find any effect on DMI when corn DDGS replaced corn grain at levels up to 40% (DM basis).…”
Section: Finishing Performancementioning
confidence: 91%
See 1 more Smart Citation
“…a, b Within a row, means lacking a common letter differ (PB0.05). (Buckner et al 2008) and WDDGS up to 60% DM did not alter DM intake of beef cattle. Although palatability of TDDGS did not appear to be a factor in the present study, Schauer et al (2005) proposed that palatability issues may reduce the intake of CDDGS when it exceeds more than 20% of the diet.…”
Section: Growth Performancementioning
confidence: 72%
“…In contrast to findings with lambs, CDDGS has been shown to increase ADG when fed to cattle. A trend toward a quadratic response in ADG was observed by Buckner et al (2008) when steers were fed CDDGS in place of dry-rolled corn at 0, 10, 20, 30 or 40% of diet DM, with ADG highest at 20% CDDGS. Other researchers have reported that replacing dry-rolled corn with CDDGS at 30% (Al-Suwaiegh et al 2002) or 40% (Ham et al 1994) of diet DM increased ADG by finishing cattle.…”
Section: Growth Performancementioning
confidence: 95%